Hubungan Pengetahuan dan Kepatuhan Penggunaan APD terhadap Kecelakaan Kerja di PT. XY - Zairinayati (IKesT Muhammadiyah Palembang, 2024)
Background: Work accidents caused by human actions that do not meet safety standards are referred to as unsafe human actions, such as not wearing personal protective equipment (PPE), working outside of procedures, working near moving or rotating machinery, fatigue, boredom, and so on. Meanwhile, accidents caused by unsafe environmental conditions are referred to as unsafe conditions, such as machines without safety features and the continued use of equipment that is no longer in good condition. The purpose of this research is to determine the relationship between knowledge and compliance with the use of personal protective equipment (PPE) and workplace accidents at PT. XY. This research method employs an observational approach with a cross-sectional design. The population in this study, taken from the Track Department of the Plant, consists of 30 workers, and the sample is the total population of 30 workers. The instruments used in this data collection are questionnaires and observations for the use of Personal Protective Equipment (PPE) as well as documentation. The research results showed that the average knowledge was poor for 16 individuals, and the average compliance was lacking for 17 individuals. Based on the bivariate analysis using Chi-Square, it was found that there is a relationship between knowledge and the use of personal protective equipment (PPE) with a P value of 0.021, and there is a relationship between compliance in using PPE and workplace accidents with a P value of 0.042. The conclusion of this study is that there is a significant relationship between knowledge and compliance in using PPE concerning workplace accidents.